Resveratrol Inhibits Pseudorabies Virus Replication by Targeting IE180 Protein - Chen, Xiangxiu; Song, Xu; Li, Lixia; Chen, Yaqin; Jia, Renyong; Zou, Yuanfeng; Wan, Hongping; Zhao, Ling; Tang, Huaqiao; Lv, Cheng; Zhao, Xinghong; Yin, Zhongqiong (Frontiers in Microbiology, 2022)
Resveratrol is a natural polyphenolic product in red wine and peanuts and has many pharmacological activities in humans. Our previous studies showed that resveratrol has good antiviral activity against the pseudorabies virus (PRV). However, little is known about the antiviral mechanism of resveratrol against PRV. In this study, we found that resveratrol inhibited the nuclear localization of IE180 protein, which is an important step for activating early/late genes transcription. Interestingly, the results show that resveratrol inhibited the activity of IE180 protein by dual-luciferase assay. Furthermore, molecular docking analysis shows that resveratrol could bind to the Thr601, Ser603, and Pro606 of IE180 protein. Point mutation assay confirmed that resveratrol lost its inhibition activity against the mutant IE180 protein. The results demonstrate that resveratrol exerts its antiviral activity against PRV by targeting the Thr601/Ser603/Pro606 sites of IE180 protein and inhibiting the transcriptional activation activity of IE180 protein. This study provides a novel insight into the antiviral mechanism of resveratrol against herpes viruses.